Brašov charter of Ivan Sracimir: a small document of great importance - Walczak-Mikołajczakowa, Mariola (Balcanica Posnaniensia. Acta et studia, 2022)
The so-called Brašov charter is a document that came out of the chancellery of the last Bulgarian ruler, Ivan Sracimir, at the end of the 14th century. This small text of only 7 lines is an example of a medieval international agreement based on Byzantine models. In it, the Tsar grants tax exemption to the merchants of Brasov, gives them trading freedoms and guarantees his protection. Despite its modest size, Ivan Sracimir’s charter has been the subject of heated discussions among scientists of various fields for years. The article reviews the findings so far on the date of its creation, the meaning of the content it contains, the graphics used, and most importantly the language. It is also the first time that the content of Brasov charter has been translated into Polish.